2010
DOI: 10.1097/brs.0b013e3181ba0b0c
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Insertion Technique on the Pullout Force of Pedicle Screws

Abstract: Undertapping of a pilot-hole either using a tap or another screw can increase the pullout strength of self-tapping pedicle screws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
39
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 20 publications
3
39
0
7
Order By: Relevance
“…Unlike the vertebral cancellous bone, the use of a pilot hole smaller than the internal (core) screw diameter should be avoided in cortical bone because it causes cortical bone fissures and microcraks that lead to bone fixation failure [39]. The increased pullout strength effect of cancellous bone compression around the pedicle screw was also observed using a tap smaller than the screw diameter or untapped screw pedicle screw insertion [7]. In our study, the pilot hole smaller (2.0 mm) than the internal diameter of the screw (2.8 mm) was randomly chosen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the vertebral cancellous bone, the use of a pilot hole smaller than the internal (core) screw diameter should be avoided in cortical bone because it causes cortical bone fissures and microcraks that lead to bone fixation failure [39]. The increased pullout strength effect of cancellous bone compression around the pedicle screw was also observed using a tap smaller than the screw diameter or untapped screw pedicle screw insertion [7]. In our study, the pilot hole smaller (2.0 mm) than the internal diameter of the screw (2.8 mm) was randomly chosen.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established in the literature that the holding power of the pedicle screw is influenced by bone mineral density [5], geometry of the screw [1,20,[25][26][27] and the screw insertion technique employed by the surgeon [5,14,33,38]. It has been reported that the holding power of the pedicle screw is significantly influenced by the size and technique of the pilot hole [5,7,14,15,33]. For selftapping cylindrical pedicle screws, reduction of the pilot hole diameter in relation to the screw outer diameter increases screw pullout force; however, the correlation of the pilot hole with screw internal (core) diameter was not mentioned [4,6,12,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary results indicated that the above mentioned numerical procedure can satisfactory simulate the influence of radial compaction as this is realized by undertapping [32].…”
Section: Discussionmentioning
confidence: 99%
“…Existing experimental studies indicate that a screw's pullout force increases linearly with increasing Title shear strength of its hosting material (Chapman et al, 1996). The fixation strength of a screw is also influenced by the design of the screw (Krenn et al, 2008, Inceoglu et al, 2008, Gefen, 2002, Chatzistergos et al, 2010a) and the insertion technique used by the surgeon (Conrad et al, 2005, Chatzistergos et al, 2010b). …”
Section: Introductionmentioning
confidence: 99%